Pengaruh Pendapatan Pegadaian, Tingkat NPL, Tingkat Inflasi dan Harga Emas Tehadap Penyaluran Pembiayaan Gadai Rahn Pada Pegadaian Syariah - Mochamad Iqbal Aulia; Iwan Setiawan (Journal of Applied Islamic Economics and Finance, 2020)
There are internal and external influences that affect the distribution of financing in sharia pawnshops and in this study there is a phenomenon that is an increase in the distribution of rahn mortgage financing followed by a decrease in income, an increase in the level of NPL, an increase in the inflation rate, and a decline in gold prices. This study aims to analyze factors that are thought to have an influence on rahn financing, namely mortgage income, NPL level, inflation rate, and gold price. This research method is a multiple linear regression method and a classic assumption test. The results of this study are not the influence of pawnshop income on the distribution of rahn pawn financing and significantly influence the level of NPL, inflation rate, and the price of gold on the distribution of mortgage financing rahn. So that in the future can be a reference consideration in the distribution of rahn financing on sharia pawnshops based on these influential factors.